2021
DOI: 10.1038/s41467-021-22921-7
|View full text |Cite
|
Sign up to set email alerts
|

Lying in wait: the resurgence of dengue virus after the Zika epidemic in Brazil

Abstract: After the Zika virus (ZIKV) epidemic in the Americas in 2016, both Zika and dengue incidence declined to record lows in many countries in 2017–2018, but in 2019 dengue resurged in Brazil, causing ~2.1 million cases. In this study we use epidemiological, climatological and genomic data to investigate dengue dynamics in recent years in Brazil. First, we estimate dengue virus force of infection (FOI) and model mosquito-borne transmission suitability since the early 2000s. Our estimates reveal that DENV transmissi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 78 publications
4
45
0
1
Order By: Relevance
“…Although variations in dengue incidence are expected, this drop in cases raises some questions, such as a possible influence of the Zika virus (ZIKV) epidemic that took place in Brazil and Latin America in the year of 2016. This epidemic was followed by a dramatic decrease of dengue and Zika cases in 2017 and 2018 [ 38 , 39 ]. Several hypotheses were considered as possible explanations, such as changes in epidemiological surveillance systems, cross-immunity and impact of climate change and multiple arboviruses in mosquito population [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although variations in dengue incidence are expected, this drop in cases raises some questions, such as a possible influence of the Zika virus (ZIKV) epidemic that took place in Brazil and Latin America in the year of 2016. This epidemic was followed by a dramatic decrease of dengue and Zika cases in 2017 and 2018 [ 38 , 39 ]. Several hypotheses were considered as possible explanations, such as changes in epidemiological surveillance systems, cross-immunity and impact of climate change and multiple arboviruses in mosquito population [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…This epidemic was followed by a dramatic decrease of dengue and Zika cases in 2017 and 2018 [ 38 , 39 ]. Several hypotheses were considered as possible explanations, such as changes in epidemiological surveillance systems, cross-immunity and impact of climate change and multiple arboviruses in mosquito population [ 38 ]. In a previous debate, the protective cross-immunity generated by the simultaneous circulation of more than one type of arboviruses was considered as the most probable explanation by a panel of experts [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the immune interaction among Flaviviruses may be more complex than expected. A DENV2 outbreak of unprecedented magnitude was reported in Nicaragua in 2019 and its severity was linked to previous ZIKV exposure [ 51 ], yet a similar pattern was not observed in other countries heavily affected by the outbreak [ 52 ]. The circumstances by which ZIKV immunity might confer protection against DENV or mediate pathogenesis are not entirely clear, although rapid waning of antibody responses may contribute to these different outcomes [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…albopictus strains have shown that local mosquitoes are more susceptible to CHIKV than to DENV [36]. This may contribute to explaining why large outbreaks of CHIKV have occurred in countries like Italy despite the fact that the number of imported CHIKV infections is, by far, much lower than the number of imported DENV cases in Europe [37,38]. However, autochthonous transmission of DENV in the last decade in continental Europe has been reported almost every year since 2013, with several countries experiencing different local transmission events in the same year [5].…”
Section: Discussionmentioning
confidence: 99%